Discovery of the biostimulant effect of asparagine and glutamine on plant growth in Arabidopsis thaliana - Lardos, Manon; Marmagne, Anne; Bonadé Bottino, Nolwenn; Caris, Quentin; Béal, Bernard; Chardon, Fabien; Masclaux-Daubresse, Céline (Frontiers in Plant Science, 2024)
Protein hydrolysates have gained interest as plant biostimulants due to their positive effects on plant performances. They are mainly composed of amino acids, but there is no evidence of the role of individual of amino acids as biostimulants. In this study we carried out in vitro experiments to monitor the development of Arabidopsis seedlings on amino acid containing media in order to analyse the biostimulant properties of the twenty individual proteinogenic amino acids. We demonstrated that proteinogenic amino acids are not good nitrogen sources as compared to nitrate for plant growth. Biostimulant analyses were based on leaf area measurements as a proxy of plant growth. We developed the Amino Acid Use Efficiency index to quantify the biostimulating effect of individual amino acids in the presence of nitrate. This index allowed us to classify amino acids into three groups, characterized by their inhibiting, neutral, and beneficial effects regarding leaf area. Glutamine and asparagine demonstrated the most significant effects in promoting leaf area in the presence of nitrate supply. The stimulating effect was confirmed by using the L and D enantiomeric forms. Both L-glutamine and L-asparagine stimulated leaf area at low concentrations, emphasizing their biostimulating properties. Our plant growth design and AAUE index pave the way for the identification of other bioactive molecules in protein hydrolysates and for the comparison of biostimulant performances.